Hubungan Self-Esteem dengan Kecenderungan Bulimia nervosa pada Remaja Perempuan: Review Naratif - Alifia Ardhani, Dea; Surjaningrum, Endang Retno (Buletin Riset Psikologi dan Kesehatan Mental, 2024)
Low self-esteem has been hypothesized as a risk factor for the development of eating disorders, with the majority of bulimia sufferers being female adolescent. This study aims to investigate the relationship between self-esteem and the tendency toward bulimia nervosa in female adolescent globally. The study shows that several previous studies have proven that one of the causes of the tendency toward bulimia nervosa is low self-esteem. The results of this study indicate that there is a relationship between self-esteem and the tendency toward bulimia nervosa eating disorder in female adolescent. It can be concluded that low self-esteem can make individuals more vulnerable to experiencing bulimia nervosa eating disorders.